Lanskap Linguistik di Kolam Renang Malindo: Pola dan Representasi dalam Konteks Multibahasa - Al Abidah, Robi’ah Al Adawiyah; Mazidah, Eva; Masruroh, Lailatul (Jurnal Studi Multidisiplin Qomaruna, 2025)
This research examines the linguistic landscape (LL) of Malindo Swimming Pool, a multilingual public space in Gresik, to explore patterns and representation of language use and their cultural implications. Using qualitative methods, including visual documentation and content analysis, the research identifies the functions and representations of languages in signage. Findings reveal that Bahasa Indonesia dominates practical signs, ensuring clarity for local visitors, while English is strategically employed for branding and inclusivity, appealing to a broader audience. Notably, the absence of regional languages like Javanese highlights a prioritization of national and international communication. Semiotic analysis uncovers the denotative and connotative meanings in the LL, reflecting modernity, cultural identity, and social dynamics. This research contributes to understanding multilingualism in public recreational spaces and provides insights for managing linguistic diversity in tourism settings.